Perfil espacial e temporal de poluentes nas águas da represa municipal de São José do Rio Preto, São Paulo, Brasil - Melo, Camila de Almeida [UNESP]; Moreira, Altair Benedito [UNESP]; Bisinoti, Márcia Cristina [UNESP] (Sociedade Brasileira de Química, 2009)
In this manuscript, seasonal and spatial trends of water collected from two sampling places in the Preto River in the Turvo-Grande watershed were evaluated. Water samples were collected during June/07 to July/08 and parameters sulphate, total organic carbon, ammonia, conductivity, dissolved oxygen, temperature, dissolved total solids and nitrate were quantified. Seasonal trend indicated sanitary effluents as a point source of contamination in both sampling points. Vertical trends demonstrated that the Municipal Dam was not stratified and received a diffuse source of pollutants from flooding and agriculture runoffs. It was also verified that there is relatively fast ammonia consumption kinetics having a half-life time of 1.43 h which can explain the low ammonia concentrations found in these aquatic bodies.
Seasonal and spatial trend of pollutants in the waters of the São José do Rio Preto municipal dam, São Paulo state, Brazil
Keywords: Preto river; seasonal and spatial trends; pollutants